PERANCANGAN WEBSITE COMPANY PROFILE MENGGUNAKAN DESIGN SCIENCE RESEARCH METHODOLOGY (DSRM) - Mira Orisa; Ahmad Faisol; Mochammad Ibrahim Ashari (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
The development of software and hardware in the field of information technology makes access to information unlimited. A website is an internet application that can be accessed by almost all people today. The benefit of a contractor company like PT. Dinamika Indonesia Presisi using the company profile website is that it notifies service users of the company's existence while also increasing the company's attractiveness to potential users.The company profile website contains a menu about us, clients, services, a portfolio, and a contact us menu. Information system design uses the design science research methodology (DSRM) method. This method combines principles, practices, and procedures so that it can make it easier for researchers to focus on solutions to problems that exist at PT. Dinamika Indonesia Presisi and help design the creation of the company profile web application for the company. Web applications are built using the HTML and CSS programming languages to make the website look more attractive.